CLONING AND EXPRESSION OF CHAETOMIUM THERMOPHILUM XYLANASE 11-A GENE IN PROKARYOTE - Wajid, S.; Latif, F.; Afzal, S.; Mukhtar, Z.; Ghaffar, A.; Mansoor, S.; Rajoka, I. (The Nucleus, 2020)
The xylanase gene was cloned into pET32a(+) and expressed in E. coli BL21 under T7 promotor alongwith fusion protein. The SDS-PAGE and western blot analysis showed a protein of ~42 kDa. The best expression of xylanase enzyme was found by using xylose as carbon source and lactose as an inducer. The maximum activity of xylanase expressed in E. coli was 6.02 U/mL in the presence of 2 % xylose in DS medium. The activity of recombinant xylanase was observed on 1 % xylan LB agar plates, showed halos of xylan clearance when lactose was used as an inducer.